2019
DOI: 10.1111/jpi.12599
|View full text |Cite
|
Sign up to set email alerts
|

STAT1‐NFκB crosstalk triggered by interferon gamma regulates noradrenaline‐induced pineal hormonal production

Abstract: Melatonin production by pineal glands is modulated by several immune signals. The nuclear translocation of nuclear factor kappa‐B (NFκB) homodimers, lacking transactivation domains, once induced by lipopolysaccharide (LPS) or tumor necrosis factor (TNF), inhibits the expression of Aanat gene and the synthesis of noradrenaline (NA)‐induced melatonin. Interferon gamma (IFN‐γ), on the other hand, increases melatonin synthesis. Furthermore, this cytokine activates the signal transducer as well as the activator of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 53 publications
(131 reference statements)
3
27
0
Order By: Relevance
“…In contrast, hyperglycemia-activated NF-κB was inhibited by Exenatide. These results demonstrate that Exenatide exerts protective effects on cardiomyocytes through the NF-κB signaling pathway, in agreement with previous studies [42,43]. Indeed, such studies have shown that inhibition of NF-κB prevents heart inflammation [44,45] while improving oxidative stress and countering the downregulation of anti-oxidative factors [46,47].…”
Section: Agingsupporting
confidence: 92%
“…In contrast, hyperglycemia-activated NF-κB was inhibited by Exenatide. These results demonstrate that Exenatide exerts protective effects on cardiomyocytes through the NF-κB signaling pathway, in agreement with previous studies [42,43]. Indeed, such studies have shown that inhibition of NF-κB prevents heart inflammation [44,45] while improving oxidative stress and countering the downregulation of anti-oxidative factors [46,47].…”
Section: Agingsupporting
confidence: 92%
“…Although our experimental setup is in time-course with this study, it is possible that methodical differences, such as culturing conditions or dosing, could differ from our study. In support, a recent study shows that IFN-γ enhances the aa-nat mRNA in the dose 100 ng/mL, but the dose 30 ng/mL has no effect [ 60 ]. Furthermore, in ewes, the direction of the response of pineal AANAT to intracerebroventricular injection of IL-1𝛽 depends on the photoperiod [ 61 ], suggesting more complex interactions between the immune system and the melatonin synthetic pathway.…”
Section: Discussionmentioning
confidence: 81%
“…GSK3β inhibition has reciprocal positive interactions with melatonin, with melatonin increasing the PI3K/Akt and ser9 phosphorylation and inhibition of GSK3β and GSK3β inhibition suppressing IDO [174]. However, a STAT1 binding site is present in the AANAT promotor [177], allowing STAT1 activation of IDO by IFNγ to induce the melatonergic pathway and melatonin release. It is likely that the concurrent release of melatonin would negatively feedback on the IFNγ/GSK3β/JAK1/PKCδ/STAT1/IDO, although AhR/CYP1B1 via the backward conversion of melatonin to NAS would have contrasting effects via TrkB activation.…”
Section: O-glcnacylation: Glycogen Synthase Kinase (Gsk)3β and Cytolytic Cellsmentioning
confidence: 99%